A new high performance PBV-based approach for simultaneous packet classification and conflict detection. (8th June 2011) - Jalalkamali, Hoda; Naji, Hamid Reza
In this paper, the searching speed of one of the algorithms for packet classification – the parallel bit vector algorithm – is increased. This is done by pre-computing the lookup step of the algorithm. Then by applying cache memory techniques, the required memory of the proposed approach is reduced. The result of internet traffic modelling analysis shows that the proposed algorithm has good performance in edge routers where the locality reference principal dominates. Our algorithm could be used for conflict detection as well at cost of reduction in performance.